Multiagent system technologies : 13th German Conference, MATES 2015, Cottbus, Germany, September 28-30, 2015. Revised selected papers /: 13th German Conference, MATES 2015, Cottbus, Germany, September 28-30, 2015. Revised selected papers. (2015) - Unknown
No abstract available